Issues on accessibility and equity in the Malaysian higher education : The roles of distance education – an overview / Norhayati Mohd Salleh and Fadilah Yahya - Mohd Salleh, Norhayati; Yahya, Fadilah (Universiti Teknologi MARA Cawangan Pahang, 2011)
Malaysia can be considered successful in providing increased access to higher education because since achieving its independence in 1957, the number of students in higher education increased to about 0.74 million in 2005 with the increase in the number of universities and higher learning institutions. This figure only represents 24% of the country’s population for the age group of 17 – 23, despite the 40% target projected for 2020. Other major concerns in Malaysia are to improve accessibility to higher education, and to ensure equity so that those belonging to the under–privileged or living in rural areas are not deprived of higher education. Without sacrificing quality, expanding the student intake capacity and providing financial support are some of the steps that have been taken thus far to balance accessibility and equity in higher education. This paper reviews the present position of the accessibility and equity in the Malaysian higher education, as well as, examines the possible role of Distance Learning to further improve flexibility in higher education.